Management of Emergency Department Services at a Secondary Level Hospital - Yesmin, Thamina; Shaheen, Shafia; Rahman, Mohammad Saeedur; Ferdouse, Mashruba; Ferdous, Jannatul; Rahman, Tayeba; Akter, Farzana; Mohammad, Nurunnabi (Journal of Monno Medical College, 2024)
Background: The primary purpose of the Emergency Department (ED) is to provide immediate medical attention and resuscitation to seriously ill patients. Prompt treatment and efficient service management play crucial roles in preventing fatalities and disabilities. Objective: To evaluate the management of emergency department services at a secondary-level hospital in Bangladesh. Methodology: A descriptive cross-sectional study was carried out in the emergency department at Narayanganj General Hospital from January to December 2018. The study involved 229 participants, including both service recipients and providers. Data was collected using a pre-tested, semi-structured questionnaire administered through face-to-face interviews. Results: The majority of participants easily identified the ED room (82.3%) and waited ≤15 minutes (91.2%) to see a doctor. They also felt that doctors listened attentively to their complaints (88.9%) and behaved well (92.5%). Service providers' behavior was also positively rated by patients, with 90.8% expressing satisfaction. Most patients did not receive all prescribed medicines from the pharmacy (81.4%), expressed dissatisfaction with the cleanliness of the environment (52.1%), and facilities in the waiting room (60.0%). Despite these concerns, they mostly stated satisfaction with the treatment received (51.6%) and the overall management of the ED (45.1%). Service providers identified several shortcomings across multiple areas, such as laboratory facilities (78.6%), staffing levels of doctors (78.6%), nurses (64.3%), and supporting staff (85.7%). Despite these challenges, they expressed satisfaction (64.3%) with their roles. Conclusion: The study demonstrated that both service recipients and service providers were satisfied with the management of medical services. However, hospital administration and health service providers should prioritize resolving deficiencies in order to improve patient satisfaction more substantially. Journal of Monno Medical College June, 2024; 10 (1):36-42